Incidence of pulmonary hypertension and determining factors in patients with systemic sclerosis - Coghlan, J. Gerry; Harutyunova, Satenik; Benjamin, Nicola; Fischer, Christine; Grünig, Ekkehard (The European respiratory journal, 2018)
The objective of this study was to evaluate the incidence of pulmonary hypertension (PH) and determining factors in patients with systemic sclerosis (SSc) and a diffusing capacity of the lung for carbon monoxide (DLCO) <60% predicted. - In this bicentric, prospective cohort study, patients with SSc were clinically assessed at baseline and after 3 years, including right heart catheterisation (RHC). Analysis of determining factors for the development of PH was performed using univariate and multivariate analyses. - 96 patients with a mean pulmonary arterial pressure (mPAP) <25 mmHg at baseline were followed for 2.95±0.7 years (median 3 years). Of these, 71 had a second RHC; 18 of these 71 patients (25.3%) developed PH, and five (7%) developed SSc-associated pulmonary arterial hypertension. For patients with an mPAP of 21-24 mmHg at baseline, the likelihood of presenting with PH as opposed to normal pressures on follow-up was significantly higher (p=0.026). Pulmonary vascular resistance, tricuspid regurgitation velocity, diffusion capacity and the size of the inferior vena cava at baseline were independent predictors for the development of PH during follow-up. - In a selected cohort of SSc patients with a DLCO <60%, pulmonary pressures appeared to rise progressively during follow-up. In this population, it was possible to identify manifest PH in almost 25% of patients using prospective RHC during follow-up. Therefore, regular clinical assessment including RHC might be useful in patients with SSc. - Tweetable abstract ERSpublications - click to tweetBorderline elevation of mPAP is associated with higher incidence of pulmonary hypertension in high-risk systemic sclerosis patients http://ow.ly/stXU30iyzrU